2014
DOI: 10.1080/17518253.2014.895859
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of bactericidal cold cream against clinical pathogens using Cassia auriculata flower extract-synthesized Ag nanoparticles

Abstract: A simple formulation of bactericidal cold cream using the biosynthesized silver nanoparticles (AgNPs) from Cassia auriculata flower extract and their antibacterial activity was tested against various clinical pathogens such as Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Staphylococcus epidermidis. An ecofriendly method was followed for the biosynthesis of AgNPs using C. auriculata flower extract as a reducing agent at room temperature. The effect of different concentrations of flower e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Some studies have been made for the production of nanoparticles by using plant extracts: Achillea biebersteinii [10], Cassia auriculata [11], Acacia farnesiana [12], Gloriosa superba [13], Alternanthera dentata [14], Cocos nucifera [15], and so forth. However very few studies were found for synthesis of nanoparticles by using peroxidase enzyme.…”
Section: Journal Of Chemistrymentioning
confidence: 99%
“…Some studies have been made for the production of nanoparticles by using plant extracts: Achillea biebersteinii [10], Cassia auriculata [11], Acacia farnesiana [12], Gloriosa superba [13], Alternanthera dentata [14], Cocos nucifera [15], and so forth. However very few studies were found for synthesis of nanoparticles by using peroxidase enzyme.…”
Section: Journal Of Chemistrymentioning
confidence: 99%
“…Nanotechnology, is special branch of material science where bulk materials break down to small particles within the range of 1–100 nm in diameter by means of physical, chemical and biological methods. Nanotechnology is absolutely a new emerging field, and basically there are evidences of several negative effects on growth and development of plantlets [16] but due to its diverse application in various fields such as DNA sequencing, pharmaceuticals, cosmetics, agriculture, biomolecular detection and diagnostics [17], it has gained attention and synthesized and used extensively in various field. Research has shown both silver and gold nanoparticles can be synthesized easily has many applications which makes it easily accessible and quite popular among researchers.…”
Section: Introductionmentioning
confidence: 99%
“…However, those methods always involve utilization of toxic reagents and expensive instruments along with the tedious process control. Therefore, there is great demand for developing a simple and green method for synthesizing ZnO NPs (19,20). Recently, biosynthesis of NPs was attracted considerable attention due to its simplicity, low cost and nontoxicity.…”
Section: Introductionmentioning
confidence: 99%